Pin1 Plays a Critical Role as a Molecular Switch in Canonical BMP Signaling. Issue 3 (March 2015) - Yoon, Won‐Joon; Islam, Rabia; Cho, Young‐Dan; Ryu, Kyung‐Min; Shin, Hye‐Rim; Woo, Kyung‐Mi; Baek, Jeong‐Hwa; Ryoo, Hyun‐Mo
<x xml:space="preserve">Abstract</x> Pin1 is a peptidyl prolyl cis‐trans isomerase that specifically binds to the phosphoserine–proline or phosphothreonine–proline motifs of numerous proteins. Previously, we reported that Pin1 deficiency resulted in defects in osteoblast differentiation during early bone development. In this study, we found that adult Pin1‐deficient mice developed osteoporotic phenotypes compared to age‐matched controls. Since BMP2 stored in the bone matrix plays a critical role in adult bone maintenance, we suspected that BMP R‐Smads (Smad1 and Smad5) could be critical targets for Pin1 action. Pin1 specifically binds to the phosphorylated linker region of Smad1, which leads to structural modification and stabilization of the Smad1 protein. In this process, Pin1‐mediated conformational modification of Smad1 directly suppresses the Smurf1 interaction with Smad1, thereby promoting sustained activation of the Smad1 molecule. Our data demonstrate that post‐phosphorylational prolyl isomerization of Smad1 is a converging signal to stabilize the Smad1 molecule against the ubiquitination process mediated by Smurf1. Therefore, Pin1 is a critical molecular switch in the determination of Smad1 fate, opposing the death signal transmitted to the Smad1 linker region by phosphorylation cascades after its nuclear localization and transcriptional activation. Thus, Pin1 could be developed as a major therapeutic target in many skeletal diseases. J. Cell. Physiol. 230: 640–647, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company